Literature in the discourse of the humanities - Глотов, Олександр Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The author suggests that the vast majority of works of world literature contains material to illustrate basic scientific postulates of the humanities: history, sociology, psychology, philology, law, etc. In particular, the article analyzes the stories and characters of the key works of world literature throughout its existence from the point of view of morality and law. Most authors build their works on offense heroes moral and legal norms.